Change or Consistency? A Historical Overview of South Africa's Post-apartheid Foreign Policy (The Strategic Review for Southern Africa, 2020)
This study examines the trajectory of South Africa's post-apartheid foreign policy by establishing the extent of change or consistency in its implementation since 1994. Under the ruling African National Congress (ANC), South Africa has emerged as a promising international actor, particularly within the Southern African region and on the African continent in general. The authors provide a historical analysis of the major trajectories of foreign policy articulation under the administrations of Presidents Nelson Mandela, Thabo Mbeki and Jacob Zuma spanning the period 1994 to 2018. In investigating the conception and execution of foreign policy under these dispensations, the authors unravel a consistent but skewed pattern of national role conception that underscores Pretoria’s vision to be a major actor in international affairs, both regionally and globally. We conclude that South Africa’s foreign policy during this period was marked by Mandela’s altruism, Mbeki’s Afrocentrism and the antediluvian signature of Zuma.
Keywords: post-apartheid; 1994; hange or consistency in its implementation; residents Nelson Mandela, Thabo Mbeki and Jacob Zuma; 1994 to 2018; dispensations; Afrocentrism; altruism; foreign policy; South Africa